Sustainable Dyeing of Cotton, Silk, and Wool Using Natural Dyes from Lawsonia inermis (Henna) and Mentha spicata (Mint): Extraction, Optimization, and Multifunctional Assessment - Yasir, Albashir; Gumel, Sani Muhammad; Joshua, Solomon; Abdulkarim, Aminu; Ela, Sule Erten; Umar, Hauwa yahaya; Joji, Umar; Aliyu, Abdulhamid Ahmad (FUDMA Journal of Sciences, 2026)
The present study investigates sustainable extraction and application of natural dyes from Lawsonia inermis (henna) and Mentha spicata (mint) for dyeing cotton, silk, and wool substrates. Dye extraction was optimized using direct heat (DH), ultrasonic bath (USB), and ultrasonic probe (USP) methods. USP extraction yielded the highest colorant recovery and superior color strength with henna 78 ± 3.1%, mint 72 ± 2.6%, compared to USB (63 ± 2.5% and 58 ± 2.3%) and DH (48 ± 2.1% and 42 ± 1.8%). FTIR confirmed hydroxyl, carbonyl, and aromatic groups associated with polyphenols, flavonoids, and tannins. Color strength (K/S values) was highest for silk (henna 15.6, mint 12.2), followed by wool (14.9, 11.5) and cotton (12.5, 9.8). The dyed substrates were further evaluated for color fastness, antibacterial activity, and UV protection. Henna extracts imparted darker shades with stronger antibacterial properties, while mint extracts contributed softer tones with moderate antibacterial effects. Both dyes enhanced UV protection, with silk demonstrating the highest dye uptake. Color fastness tests showed good wash, rubbing, and perspiration resistance (ratings 3–5). Henna-dyed fabrics exhibited stronger antibacterial activity, with inhibition zones up to 20 mm against S. aureus and 18 mm against E. coli, compared to mint (15 mm and 14 mm, respectively). Both dyes improved UV protection, with UPF values ranging from 25 (cotton-mint) to 40 (wool-henna). These findings highlight henna and mint as eco-friendly alternatives to synthetic dyes, providing multifunctional benefits of coloration, antibacterial efficacy, and UV protection within the framework of green chemistry.